Bibliographie analytique de l'Afrique antique XLVII (2013) - Coltelloni-Trannoy, Michèle; Briand-Ponsart, Claude; Pons Pujol, Lluís; Rocca, Elsa; Villey, Thomas; Guédon, Stéphanie (Bibliographie analytique de l'Afrique antique (BAAA), 2019)
undefined